Factors influencing customer acceptance towards electronic wallets (e-wallets) in Malaysia: perceived security as focus variable - Abu Bakar, Nashirah; Rosbi, Sofian; Norizan, Siti Noraisyah; Mohd Yusoff, Marmeezee; Ali, Muhammad Ahmar (Asian Scholars Network, 2024)
An electronic wallet is a form of online service that facilitates the electronic transfer of funds through the utilization of Internet connectivity. The utilization of electronic wallets has been expanded to encompass a wide range of online activities, including the facilitation of purchasing transactions through e-commerce platforms. From the data collected by the Statistica Research Department, from 2020 until May 2023, the number of e-commerce scams in Malaysia is 19, 252 cases. In addition, Malaysia saw a drastic increase in online scams over the last two years during the COVID-19 pandemic. According to the Royal Malaysia Police (PDRM) Commercial Crimes Investigation Department (CCID), a total of 71,833 scams, amounting to more than RM5. 2 billion in losses, were reported from 2020 until May 2022. This situation creates a need to perform research that addresses this problem. Therefore, this study explored the perception of security factors linked to the acceptance of e-wallet usage among Malaysian customers. This study uses a quantitative research method with a questionnaire. The underpinning theory is the Technology Acceptance Model (TAM), which consists of two variables namely perceived usefulness (PU) and Perceived Ease of Use (PEOU). This theory is widening by including one additional variable, Perceived Security (PS). Then collected data were analysed using structural equation modeling. The population is Malaysian consumers who use e-wallet. The number of samples is 150 respondents. The finding shows all three variables are significant in increasing the adoption of e-wallets among Malaysian consumers. The findings of this study help e-wallet providers to develop better facilities to meet the customers' expectations. At the same time, this study provides insight to the central bank to develop policy on the security aspects of e-wallet services. This study also exposes the public to financial literacy of security for e-wallet usage to prevent deceived by scam activities.